RESEARCH ON THE EFFECTIVENESS OF SOME INSECTICIDES IN COMBATING PESTS IN AN OAT CROP - Alexandru POPA; Cristinel Relu ZALĂ; Rada ISTRATE; Mihai GÎDEA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The behavior of oat varieties against harmful insects is an essential agronomic property. In the protection of plants in general and in oat culture, in the present case, insecticides will be applied only at the times when they are needed and in the optimal doses. In addition to respecting the technological links (quality ploughing, crop rotation, sowing in the optimal season), combating oat pests is a priority to minimize quantitative and qualitative production losses. In this work, the identified harmful species are presented: Sitobion avenae, Helicoverpa armigera, Haplodiplosis marginata, Haplothrips tritici, Agrotis segetum, Phorbia fumigata and mites,as well as the effectiveness of insecticide treatments based on cypermethrin 00 g/liter (Faster 0 CE), lambda-cyhalothrin 50 g/liter (Karate Zeon® 50 CS) and deltamethrin 00 g/liter (Decis® Expert 00 EC) against them. The research was carried out under conditions of natural infestation of the Ovidiu variety, during the vegetation period of 202 in Mircea Vodă commune, Brăila county. Among these species, the greatest abundance was represented by the species Sitobion avenae. The effectiveness of the insecticide treatments applied to the oat crop was reflected in a very significant increase in production of 325 kg/ha in the case of the Karate Zeon® 50 CS product, a distinctly significant increase of 279 kg/ha in the case of the Decis® Expert 00 EC product and a insignificant increase, of 30 kg/ha, in the case of the product Fastac 0 CE.